Diagnostic value of 64-slice CT angiography in coronary artery disease: a systematic review - Sun, Zhonghua; Lin, C.; Davidson, R.; Dong, C.; Liao, Y. (Elsevier Ireland Ltd, 2008)
Purpose: To perform a systematic review of the diagnostic value of 64-multislice CT (MSCT) angiography in the detection of coronary artery disease (CAD) when compared to conventional coronary angiography. Materials and methods: A search of PUBMED and MEDLINE databases for English literature was performed. Only studies with at least 10 patients comparing 64-slice MSCT angiography with conventional coronary angiography in the detection of CAD were included. Diagnostic value of MSCT angiography compared to coronary angiography was compared and analysed at segment-, vessel- and patient-based assessment. Results: Fifteen studies met selection criteria and were included for analysis. Pooled sensitivity, specificity, positive predictive value and negative predictive value as well as 95% confidence interval (CI) were 97% (94 and 99%), 88% (79 and 97%), 94% (91 and 97%), and 95% (90 and 99%) for patient-based assessment; 92% (85 and 99%), 92% (85 and 99%), 78% (66 and 91%) and 98% (96 and 99%) for vessel-based assessment; 90% (85 and 94%), 96% (95 and 97%), 75%(68 and 82%) and 98% (98 and 99%) for segment-based assessment, respectively. No significant difference was found in the diagnostic accuracy of 64-slice CT in the detection of CAD when comparison was performed either among four main coronary arteries, or between proximal and middle or distal segments (p > 0.05). Conclusion: Our results showed that 64-slice CT angiography has a high-diagnostic value in the detection of CAD. Severe coronary artery calcification seems to be the major factor affecting the visualisation and assessment.